Application of Stable Carbon Isotopes in a Subtropical North Atlantic MesocosmStudy: A New Approach to Assess CO2 Effects on the Marine Carbon Cycle - Esposito, Mario; Achterberg, Eric P.; Bach, Lennart T.; Connelly, Douglas P.; Riebesell, Ulf; Taucher, Jan (Frontiers in Marine Science, 2019)
Stable isotope ratio analysis offers a unique opportunity to obtain information on ecosystem processes. The increase in atmospheric CO2 as a consequence of fossil fuel combustion and land-use change is altering the stable carbon isotope composition (δ13C) of the atmosphere and ocean. This work investigates the application of using δ13C measurements of seawater samples to explore the biogeochemical responses of marine ecosystems to anthropogenic CO2 perturbations. The combination of isotopic and non-isotopic measurements from a subtropical North-Atlantic mesocosm experiment provided a holistic view of the biogeochemical mechanisms that affect carbon fluxes under a gradient of pCO2 ranging from ~350 up to ~1000 µatm during a phytoplankton succession. A clear CO2 response was detected in the isotopic datasets with 13C shifts of up to ~5 ‰, but increased CO2 levels only had a subtle effect on the concentrations of the dissolved and particulate organic carbon pools. Distinctive δ13C signatures of the particulate organic carbon pools in the water column and sediment traps were detectable for the different CO2 treatments after a nutrient stimulated phytoplankton bloom. These signatures were strongly correlated (p < 0.05) with the δ13C signatures of the inorganic carbon but not with the δ13C of the dissolved organic carbon pools (p > 0.05). Fractionation of carbon isotopes in phytoplankton was positively affected (9.6 < ε < 16.5 ‰) by high CO2 levels either because of the higher CO2 availability or because of a shift in phytoplankton community composition. Nevertheless, phytoplankton bloom intensity and development was independent of CO2 concentrations, and higher CO2 levels had no significant effect on inorganic nutrient uptake. Results from this mesocosm experiment showed that variations in the carbon isotopic signature of the carbon pools depend on both physical (air-sea exchange) and biological (community composition) drivers opening the door to new approaches for investigations of carbon cycling in marine ecosystems.